Investigating the Effect of Cognitive and Sensorimotor Exercises on the Functional Balance of the Elderly - Mahmoud Shaykh; Zinat Ayazi Vanani; Fazllolah Bagherzadeh (Shahrekord University of Medical Sciences, 2019)
Background and aims: The elderly living in nursing homes have different motor situations compared with their peers, which can affect different motor functions. Investigating the characteristics of balance has always been of interest to researchers due to its importance in the functional independence of the elderly. Thus, the present research aimed to investigate the effect of cognitive and sensorimotor exercises on the functional balance of the elderly. Methods: This quasi-experimental study was performed with the intragroup comparison design, as well as pre- and post-test measurement stages in Iran during 2017. A total of 60 elders were chosen through the convenience sampling method. Accordingly, the subjects were matched in four groups after performing the pretest with demographic, physical activity readiness, and Mini-Mental State Examination questionnaires and Tinetti test. Each group performed eight exercise situations lasting for 5-10 seconds by taking the overload principle into account throughout 24 sessions. The statistical population of this research consisted of the elderly living in nursing homes under the supervision of the Welfare Organization of Shiraz, including 875 individuals. In general, 60 subjects were chosen through a voluntary method (age: 61.7 ± 7.6 years old, weight: 65.2± 16.2 kg, and height: 157.7± 6.7 cm). During the data collection, 14 subjects left the study for different reasons. The balance characteristics were measured by the Tinetti test. Finally, statistical analysis was performed through the difference of the scores of measurement stages and by one-way ANOVA and Tukey post hoc tests. Results: The comparison of cognitive, sensorimotor, and combined groups with the control group regarding the dependent variables of the research indicated that cognitive exercises have no significant effect on balance (P=0.103), while the sensorimotor (P=0.002) and combined (P=0.002) exercises were effective on balance. Conclusion: In general, the significance of the balance following sensorimotor and combined exercises compared to the insignificance of cognitive exercises can highlight the importance of sensorimotor exercises in the balance of the elderly living in nursing homes.